2017
DOI: 10.1021/acsomega.6b00384
|View full text |Cite
|
Sign up to set email alerts
|

NiO Nanoparticle Synthesis Using a Triblock Copolymer: Enhanced Magnetization and High Specific Capacitance of Electrodes Prepared from the Powder

Abstract: Nickel oxide nanoparticles of diameter ∼21 nm were prepared by a sol–gel method using the triblock copolymer poly(ethylene glycol)- b -(propylene glycol)- b -(ethylene glycol). X-ray photoelectron spectroscopy analysis showed the presence of Ni 2+ and Ni 3+ ions in the material. The electrical conductivity of this material was due to small polaron hopping between Ni 2+ and Ni 3+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…The diffraction peaks have been identied to be those pertaining to NiO crystals. 10 Using Debye-Scherrer equation 42 viz.,…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The diffraction peaks have been identied to be those pertaining to NiO crystals. 10 Using Debye-Scherrer equation 42 viz.,…”
Section: Resultsmentioning
confidence: 99%
“…So, ferromagnetic-like behaviour in NiO nanoparticles was reported by various researchers. 10,20,[28][29][30] In this paper, it is shown that, NiO nanoparticles exhibit ferromagnetic like behaviour in contrast to antiferromagnetism at higher elds. This has been explained as arising due to the presence of uncompensated spins associated with Ni 3+ ions in the material.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations